2017
DOI: 10.1159/000467907
|View full text |Cite
|
Sign up to set email alerts
|

Proton Magnetic Resonance Spectroscopy Study on the Metabolism Changes of Cerebellum in Patients with Post-Stroke Depression

Abstract: Objective: To study the metabolic changes of cerebellum by proton magnetic resonance Spectroscopy (1H-MRS) and discuss the relationships between the cerebellar changes and depression severity in patients with post-stroke depression. Methods and Results: Data of demographic characteristics, individual history and life style of all subjects were collected. 40 patients with stroke and 20 controls were enrolled. All groups received T1WI, T2WI, DWI and 1H-MRS examination. The cerebral infarcti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This result may suggest that the pathogenesis of acute PSD was related to non-neuronal changes. Other studies also showed no differences in cerebellar NAA concentrations in PSD patients compared to a control group [ 33 , 34 ]. However, lower NAA/Cr ratio in the cerebellar hemisphere contralateral to the lesion at 3 months after stroke compared to that at 14 days after stroke indicated that, the pathogenesis of chronic PSD may be related to the abnormal function of neurons and axons, abnormal cell energy metabolism and structural damage.…”
Section: Discussionmentioning
confidence: 93%
“…This result may suggest that the pathogenesis of acute PSD was related to non-neuronal changes. Other studies also showed no differences in cerebellar NAA concentrations in PSD patients compared to a control group [ 33 , 34 ]. However, lower NAA/Cr ratio in the cerebellar hemisphere contralateral to the lesion at 3 months after stroke compared to that at 14 days after stroke indicated that, the pathogenesis of chronic PSD may be related to the abnormal function of neurons and axons, abnormal cell energy metabolism and structural damage.…”
Section: Discussionmentioning
confidence: 93%
“…17) In addition, tricyclic antidepressant drugs, such as amitriptyline and imipramine, and the SSRI paroxetine, decrease DNMT activity. 33) Therefore, medication might affect methylation-related enzymes and alter methylation levels. However, these studies were performed in the brain, not in blood.…”
Section: Discussionmentioning
confidence: 99%
“…TSH is involved in the body's metabolism and plays an important part in the development of the central nerve system, which can affect various neurologic functions, including behavior and sensation. Some studies have shown the connection between changes in TSH levels and depression [ 49 ]. The present study found obviously lower TSH levels in depressive patients than in HCs, suggesting that patients with depression may have dysfunction in TSH.…”
Section: Discussionmentioning
confidence: 99%